1986
DOI: 10.1002/ar.1092150110
|View full text |Cite
|
Sign up to set email alerts
|

A hypothesis on the allantoic origin of the distal midgut

Abstract: No satisfactory explanation for the absence of the ileocecal portion of the digestive system in the newborns with cloacal exstrophy has been offered previously. This is a report of such a case in which the lymphocytes and plasma cells were used as tissue markers to identify the origin of the lymphatic-rich ileocecal portion of the digestive tract. The absence of these cells, in this case demonstrated immunohistochemically, is suggestive of a dual origin of the midgut. Normal embryogenesis of the digestive syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(12 reference statements)
1
2
0
Order By: Relevance
“…In addition, we demontiation in the bone marrow has remained elusive (Owen strate the extreme steroid sensitivity of the cells in this et al., 1977;Osmond, 1986;Osmond and Batten, 1984). tissue, and we correlate these observations with new In addition, other experiments have indicated that bone information (Zarabi and Rupani, 1986) suggesting that marrow may not be an essential site of B cell differentia-the allantois participates in the formation of the distal tion (Phillips and Miller, 1974;Kincade et al, 1975; midgut, including its lymphoid components. Hayakawa et al, 1985).…”
supporting
confidence: 73%
See 1 more Smart Citation
“…In addition, we demontiation in the bone marrow has remained elusive (Owen strate the extreme steroid sensitivity of the cells in this et al., 1977;Osmond, 1986;Osmond and Batten, 1984). tissue, and we correlate these observations with new In addition, other experiments have indicated that bone information (Zarabi and Rupani, 1986) suggesting that marrow may not be an essential site of B cell differentia-the allantois participates in the formation of the distal tion (Phillips and Miller, 1974;Kincade et al, 1975; midgut, including its lymphoid components. Hayakawa et al, 1985).…”
supporting
confidence: 73%
“…Unfortunately, little appears to be known about cecal and colonic lymphoid tissue in these species. Similarly, the existence, extent, and ontogeny of proximal colonic lymphoid tissue in the human colon are unknown, although recently Zarabi and Rupani (1986) have shown that IgM-and IgD-positive cells could not be demonstrated in a newborn with cloaca1 exstrophy. This condition resulted in the absence of the terminal ileum, cecum, and proximal colon.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the accuracy of this statement, we reviewed the literature on exstrophy of the cloaca for lower limb defects. Of 178 reviewed cases, including the one we presented here, 63 reportedly had normal lower limbs [Hurwitz et al, 1987;Meglin et al, 1990;Evans et al, 1994;Chen et al, 1997;Liang et al, 1998;Mathews et al, 1998;Hamada et al, 1999;Keppler-Noreuil, 2001;Reddy et al, 2003], 43 gave no information about the status of the lower limbs [Hayden et al, 1973;Diamond and Jeffs, 1985;Fujiyoshi et al, 1987;McLaughlin et al, 1995;Meizner et al, 1995;Pinette et al, 1996;Kano and Ichimura, 1997;Austin et al, 1998;Nye et al, 2000], 17 had clubfeet with no further status of the lower limb given [Diamond and Jeffs, 1985;Zarabi and Rupani, 1986;Fujiyoshi et al, 1987;McLaughlin et al, 1995;Robin et al, 1996;Bruch et al, 1996;Pinette et al, 1996;Girz et al, 1998;Silver et al, 1999], 24 had clubfeet as the only lower limb anomaly [Hurwitz et al, 1987;Meglin et al, 1990;Chen et al, 1997;Liang et al, 1998;Mathews et al, 1998;Keppler-Noreuil, 2001], and 31 had major malformations of the lower limbs [Ogden, 1976;Balog and Skinner, 1984;Hurwitz et al, 1987;Meglin et al, 1990;…”
Section: Discussionmentioning
confidence: 90%